Isolated spinal Intramedullary Neurocysticercosis: A rare case report and review of literature - Lama, Subigya Man; Paudel, Kumar; Shalikhe, Narendra; Yadav, Pradhumna Kumar; Lamichhane, Somraj (Nepal Journal of Neuroscience, 2023)
Neurocysticercosis is Taenia solium infection of the central nervous system and meninges. Although highly uncommon, spinal cysticercosis frequently occurs in conjunction with intracranial cysticercosis. The least frequent are often those involving the intramedullary. We report a 50-year-old male patient who presented with complaints of lower back pain with a burning sensation over bilateral thighs. A magnetic resonance imaging (MRI) scan of his dorsal spine revealed a relatively well-defined lobulated lesion at T11 vertebral level. Intramedullary cysticercosis is a challenge to diagnose, and neurocysticercosis should also be considered in cases of intramedullary space-occupying lesion.